Force-moment interaction diagram and structural analysis of concrete bridge box girder in finite element - Muhammad Hazim, Mohd Isa (2018)
In this research, a 2D box girder has been analysed by using ANSYS software and manual calculation. This research is to determine the strain, stress, maximum deflection, deformation and also checking the structure according to Eurocode 2. As we know the uses of concrete structure in the construction is widely used. It easy to conduct and construct compare to other type of bridge. The type of material and the geometry for the structure was satisfied in in cases it passed all the designing for tensile, buckling and compression. From the result of simulation, we can know the behaviour of the structure under the input parameter that applied. 50 simulation had been made to make sure the analysis has sufficient data. Then, from the probabilistic analysis, we collect the result of cumulative distribution function, the histogram plot for input and output parameter, sensitivity plot and simple history plot for all parameter.